Fragmented Landscape of European Policies in the Energy Sector: First-Mover Advantages - Kristina Govorukha; Philip Mayer; Dirk Rübbelke (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In order to achieve the commonly agreed emission reduction target, the European Commission developed binding national targets for each member state until 2030 and called upon the member states to submit National Energy and Climate Plans to ensure increased transparency for the respective national targets and strategies. An analysis of these plans shows that some of the emission reductions set at the national level prescribe a more ambitious decarbonisation than the EU-wide limits. However, since a transformation to a climate-friendly system requires considerable investment, the question arises as to why some states apparently want to be in the vanguard. We find that countries may have an incentive to outperform other states in the development of a low-carbon electricity system in order to pass on part of the transformation costs to neighbouring countries.
Keywords: C60; Q40; 330; electricity; utilities; thermal generation; unilateral action; climate policy